Seroprevalence and associated factors for hepatitis B and hepatitis C viral infection among patients with diabetes mellitus in Northern Tanzania - Doreen T. Eliah; Nyasatu G. Chamba; Abid M. Sadiq; Amos O. Mwasamwaja; Faustini C. Kimondo; Cuthbert D. Matay; Eliada B. Nziku; Tumaini E. Mirai; Ibrahim Ali Ibrahim Muhina; Fuad H. Said; Sarah K. Gharib; Furaha S. Lyamuya; et al. (PLoS ONE, 2025)
Background The coexistence of viral hepatitis with diabetes mellitus (DM) significantly escalates the risk of severe outcomes. This study aimed to determine the seroprevalence and associated factors of hepatitis B (HBV) and hepatitis C (HCV) viral infections among DM patients in northern Tanzania. Materials and methods Conducted between February 2023 and May 2023, this hospital-based cross-sectional study enrolled 189 patients with DM from the Diabetic Clinic of Kilimanjaro Christian Medical Centre. A structured questionnaire captured relevant clinical information, and plasma blood sample was assessed for hepatitis B surface antigen and anti-hepatitis C antibody seropositivity. Data analysis employed SPSS v26, and a chi-square test was used to determine the statistical difference of HBV and HCV among patients with DM. Logistic regression was performed to determine factors associated with HBV and HCV. Results Among the 189 patients with DM, the seroprevalence of HBV and HCV infections stood at 2.1% and 0.5%, respectively. Males constituted a significant majority (80%) of those affected by viral hepatitis. Furthermore, 60% of affected patients were in non-union relationships (single, widowed, or divorced), and 40% reported multiple sexual partners. However, the study found no significant association between traditional associated factors and viral infection acquisition. Conclusion The study’s findings reveal a relatively low prevalence of HBV and HCV infections among patients with DM compared to the general population, with no significant association among factors. Nonetheless, the results underscore the importance of early screening and vaccination for HBV and HCV in patients with DM. Such efforts are crucial for curbing infection spread and reducing the risk of hepatocellular carcinoma development in this vulnerable population.